Collagenous enterocolitis and maturity onset type 1 diabetes manifesting as uraemia, malabsorption and extreme weight loss. (23rd July 2014) - Hunter, Jonathan Michael; Lee, Hui Jean; Dettrick, Andrew; Tan, Christopher
Abstract : A 37-year-old patient with type 1 diabetes had been recently diagnosed with collagenous colitis (CC) after sigmoidoscopy. She rapidly progressed from a fortnight of watery diarrhoea, to a malabsorptive state with severe dehydration and acute kidney injury. This necessitated admission to an intensive care unit for emergency dialysis. She was subsequently diagnosed with collagenous enterocolitis affecting gastric, small bowel and colonic mucosa which required systemic steroid therapy. Physicians caring for patients with CC should be aware of the potential extreme manifestations of upper gastrointestinal collagenous deposition.